Pengaruh Kinerja Keuangan Pemerintah Daerah Terhadap Alokasi Belanja Modal - Rahmadini, Dita; Indriani, Rini; Febriana, Nucke (Owner : Riset dan Jurnal Akuntansi, 2024)
This study was conducted in western Indonesian cities during 2020-2022. This study aims to determine how the influence of local government financial performance on capital expenditure in western Indonesian cities both simultaneously and partially as seen from the fiscal decentralization ratio, effectiveness ratio, and efficiency ratio. This study uses a quantitative and descriptive analysis approach. The population of this study was 64 in western Indonesian cities using nonprobability sampling technique, so the sample included 192 financial statements from 3 years of observations. As well as technical documentation collects data through the regional government director’s balance sheet website. The analytical method in this study is panel data regression. The results testing with panel data regression using the Fixed Effect Model (FEM) show that financial performance simultaneously influences capital expenditure in western Indonesian cities during 2020-2022. Figure F > F table result obtained (2.853526 > 2,65), significance (0,000000 < 0,05). From the partial test results fiscal decentralization ratio has an negative effect and significance on capital expenditure allocation, effectiveness ratio has an positive effect and significance on capital expenditure allocation, and efficiency ratio has an positive effect and significance on capital expenditure Allocation in western Indonesian cities during 2020-2022.